Incremento de la práctica de valores ambientales mediante la aplicación de las 3R’S en la población del caserío de Nina Rumi - San Juan - Iquitos - 2020 - Grandez Huayunga, Evenly (2021)
The present research work was carried out in San Juan Bautista district, village of Nina Rumi, with the aim of determining, through the 3R's technique, the improvement of the practice of environmental values in the population of the village of Nina Rumi - San Juan Bautista, Maynas province, Loreto - Peru. The research is qualitative, based on information in the collection of primary information based on surveys and interviews with those involved; Having reached the conclusion of the training given to the residents of Nina Rumi village, it went from DEFICIENT with 100.5 points to REGULAR with 126.5 points. The answer NO OPINION whose percentage in the pretest stage was 22.58% and in the posttest stage it dropped considerably to 11.97%, which implies that the population improved its degree of indifference. The answers NEVER and ALMOST NEVER in the pre-test stage exceeded 30% in all cases and in the post-test stage it dropped significantly in several points. The application of the reduce, recycle and reuse (3R's) technique has significantly improved development of the values of responsibility with the environment of the inhabitants of Nina Rumi. The results show us that the inhabitants of Nina Rumi village are immersed in a poor environmental attitude in the matter of solid waste management; therefore, it is necessary to develop solid waste management training based on the 3Rs.